1999
DOI: 10.1029/1999jd900817
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of formaldehyde, acetic acid, methanol, and other trace gases from biomass fires in North Carolina measured by airborne Fourier transform infrared spectroscopy

Abstract: Abstract. Biomass burning is an important source of many trace gases in the global troposphere. We have constructed an airborne trace gas measurement system consisting of a Fourier transform infrared spectrometer (F'FIR) coupled to a "flow-through" multipass cell (AFrlR) and installed it on a U.S. Department of Agriculture Forest Service King Air B-90. The first measurements with the new system were conducted in North Carolina during April 1997 on large, isolated biomass fire plumes. Simultaneous measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
383
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 326 publications
(408 citation statements)
references
References 65 publications
23
383
2
Order By: Relevance
“…Global NH 3 emission data taken with infrared satellite observations show that concentrations in the eastern United States are low and no significant hotspots exist in this region (Clarisse et al, 2009 (Dentener and Crutzen, 1994) and [NH 3 ] up to 430 ppbv have been seen in strong point source locations (Schlesinger and Hartley, 1992). Emission measurements made in different automobile tunnels have shown [NH 3 ] of 50-400 ppbv (Fraser and Cass, 1998;Kean et al, 2000;Moeckli et al, 2004) [NH 3 ] of 20-70 ppbv have also been reported from smoke (Yokelson et al, 1999Goode et al, 2000), as well as 100-200 ppbv in biomass burning plumes (Hurst et al, 1994;Li et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Global NH 3 emission data taken with infrared satellite observations show that concentrations in the eastern United States are low and no significant hotspots exist in this region (Clarisse et al, 2009 (Dentener and Crutzen, 1994) and [NH 3 ] up to 430 ppbv have been seen in strong point source locations (Schlesinger and Hartley, 1992). Emission measurements made in different automobile tunnels have shown [NH 3 ] of 50-400 ppbv (Fraser and Cass, 1998;Kean et al, 2000;Moeckli et al, 2004) [NH 3 ] of 20-70 ppbv have also been reported from smoke (Yokelson et al, 1999Goode et al, 2000), as well as 100-200 ppbv in biomass burning plumes (Hurst et al, 1994;Li et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The AFTIR was used for continuous measurements of water vapor (H 2 O), carbon dioxide (CO 2 ), carbon monoxide (CO), and methane (CH 4 ); or to grab samples for signal averaging and measurement of H 2 O, CO 2 , CO, nitric oxide (NO), nitrogen dioxide (NO 2 ), ammonia (NH 3 ), hydrogen cyanide (HCN), CH 4 , ethene (C 2 H 4 ), acetylene (C 2 H 2 ), formaldehyde (HCHO), methanol (CH 3 OH), acetic acid (CH 3 COOH), formic acid (HCOOH), and ozone (O 3 ). The details and the accuracy of the AFTIR technique are described by Yokelson et al (1999Yokelson et al ( , 2003a.…”
Section: Airborne Fourier Transform Infrared Spectrometer (Aftir)mentioning
confidence: 99%
“…[4] Biomass burning is an important source of atmospheric OVOCs [e.g., Holzinger et al, 1999;Yokelson et al, 1999]. In this study, we characterized the first carbon isotope signatures of methanol and acetaldehyde emitted from biomass burning sources (BB) and elucidated factors controlling their variation using small chamber burning experiments of five plant materials (three C 3 and two C 4 plants).…”
Section: Introductionmentioning
confidence: 99%